ASPEK HUKUM DIGITAL LENDING DI INDONESIA - Sugeng, Sugeng (Jurnal Legislasi Indonesia, 2020)
Financial service innovations are increasingly diverse and growing rapidly in line with the increase in information technology. Peer to peer lending (P2P Lending) is a breakthrough of financial institutions to serve various parties that need funding. This article intends to analyze the legal aspects and implementation of P2P Lending services in Indonesia. The research method uses a normative juridical approach, through the study of authoritative legal materials and supporting literature materials.  The study found that the Financial Services Authority Regulation Number 77/POJK.01/2016 concerning Information Technology-Based Money Lending and Borrowing Services, Financial Services Authority Regulation Number 13/POJK.02 /2018 concerning Digital Financial Innovation in the Financial Services Sector, Government Regulation Number 82/ 2012 concerning the Implementation of Electronic Transactions and Systems, Financial Services Authority Regulation Number: 1/ POJK.07/2013 concerning Financial Services Sector Consumer Protection are the national legal instrument that regulates this business activity. In addition, the code of ethics made by business associations also complements the regulations for organizing P2P Lending.  The lack of coordination between government agencies has led to ineffective supervision, resulting in illegal P2P Lending companies. The results of this study are expected to provide input for policy makers to improve regulations that can provide legal protection for the parties.